(untitled) (Research, Society and Development, 2022)
Biostimulants are defined as a mixture of two or more plant regulators with other substances (amino acids, nutrients and vitamins), products that can, depending on their composition, concentration and proportion of substances, stimulate plant growth through greater cell division, cell elongation and cell differentiation. The objective of this study was to define the best dose of Tonik in seed treatment in 4 cotton varieties. The experiment was developed at the Teaching, Research and Extension Farm of the UniBRAS College in Rio Verde – GO. The objective of this study was to define the best dose of Stimulate in the treatment of cotton seed of the variety 18115 FM 983 GLT. The test was carried out in pots of 10 kg of soil filled in a proportion of 3:1 soil:sand ratio. The variety 18115 FM 983 GLT with medium/late cycle (160 to 190 days) was used. The variables evaluated were: number of emerged plants (NPE) at 7 DAP; plant height (AP); stem diameter (DC), number of leaves (NF) at 14 DAP and total shoot dry matter (MSTPA) at 28 DAP. Data were submitted to analysis of variance (p<0.05) and significant cases were submitted to the regression test.